Climate Change Inaction as Violation of Human Rights: The Swiss Women Climate Case and Impact on Stock Markets - Ngwakwe, Collins, C (Acta Universitatis Danubius. Juridica, 2024)
Climate litigation has commonly been viewed as complicated by the courts and judges. Objective: this objective of this paper is to examine if climate inaction by a state constitutes and infringement on human right. It also aimed to analyse the effects of court decision on climate change litigation on global stock exchange performance. Priorwork: the paper inclines on prior literature on climate litigations and on the efficient market hypothesis of information impact on stock prices. Method: the paper applied two approaches namely a qualitative conceptual approach with the analysis recent ECHR, and brief quantitative approach using World Stock Market Index data. Results: climate change inaction by a state may constitute a violation of human right to life, quality of life and wellbeing. Also, the court decision on climate change litigation affects world index of stock markets significantly and negatively – showing that climate change litigation causes a negative jittery on stock markets. Implication: the paper offer implication for university business law departments, finance, economics and accounting academics for curriculum and research. It also offers practical implication for businesses to balancing economic risks inherent in business climate accountability. Value: the paper contributes a novel framework on climate inaction as violation of human rights and offers a new model of analysis with a combination of climate ligation and World Index of Stock Exchanges.